LA PANTALLA DE CINE ABANDONA LA SALA - David VICENTE TORRICO (Fonseca, Journal of Communication, 2023)
Last year, the cinematographic exhibition grossed 571 million Euros and congregated more than 94 million spectators. Nowadays, however, this business cannot stay at the edge of the fourth screen’s revolution, that is to say, mobile phones. In a market controlled by two big enterprises, namely Cinesa and Yelmo, we propose a qualitative study of its digital applications, considering their design, their accessibility and their features, with the goal of verifying their adaptation to this new digital environment. The results will show an emerging opening. Nevertheless, numerous services must be implemented to enhance the spectator’s cinematographic experience.